2006
DOI: 10.1385/bter:112:2:131
|View full text |Cite
|
Sign up to set email alerts
|

Blood α-Tocopherol, Selenium, and Glutathione Peroxidase Changes and Adipose Tissue Fatty Acid Changes in Kittens with Experimental Steatitis (Yellow Fat Disease): A Comparative Study Between the Domestic Shorthaired and Siamese Breed

Abstract: Twenty domestic shorthaired (DSH) and 20 Siamese (S) kittens were allocated into 4 breed-specific groups, of 10 kittens each, that were fed exclusively cooked sardines (F groups) or commercial feline canned food based on oily fish (C groups) for a 4-month period. Clinical signs were scored every 15 d along with body weight recording and blood sampling for the measurement of alpha-tocopherol and selenium (Se) concentrations and glutathione peroxidase (GSH-Px) activity. Subcutaneous adipose tissue samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…The aetiology of pansteatitis in fish and crocodiles from Loskop Dam is as yet unknown, although it is recurrently described elsewhere as being related to a diet high in polyunsaturated fats and deficient in antioxidants, in captive-bred animals (Roberts et al, 1979;Larsen, 1983;Fytianou et al, 2006;Goodwin, 2006;Roberts and Agius, 2008). The diet of Oreochromis mossambicus in Loskop Dam was investigated during the present study, but these results will be reported separately.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The aetiology of pansteatitis in fish and crocodiles from Loskop Dam is as yet unknown, although it is recurrently described elsewhere as being related to a diet high in polyunsaturated fats and deficient in antioxidants, in captive-bred animals (Roberts et al, 1979;Larsen, 1983;Fytianou et al, 2006;Goodwin, 2006;Roberts and Agius, 2008). The diet of Oreochromis mossambicus in Loskop Dam was investigated during the present study, but these results will be reported separately.…”
mentioning
confidence: 96%
“…An important piece in the pansteatitis puzzle is the increased frequency and extent of algal blooms, particularly in the transitional zone. From a fish health perspective, this represents a modified food web which may have important links to the development of pansteatitis in O. mossambicus, particularly as the disease is so often attributed to dietary causes (Fytianou et al, 2006). Generally O. mossambicus feed on a combination of detritus, phytoplankton, filamentous algae, diatoms and plant material (De Moor et al, 1985), but there are ontogenetic and site-specific differences which have not been researched in Loskop Dam.…”
mentioning
confidence: 99%
“…Fytianou et al (2006) provided experimental evidence linking the disease to the consumption of high levels of unsaturated fatty acids or oxidized fats that deplete the vitamin E.…”
Section: Discussionmentioning
confidence: 99%
“…The deaths of the crocodiles from Olifants Gorge and Sabie River were associated with steatitis, a condition affecting the fat tissue of the crocodile, causing the tissue to harden, becoming inflamed and yellow (Scott et al, 1995;Fytianou et al, 2006). Most of the crocodiles died with large but steatitic fat reserves and empty stomachs.…”
Section: Introductionmentioning
confidence: 99%